Preschool staff perceptions of leader capabilities during COVID-19 early stage in Iceland - Dýrfjörð, Kristín; Hreiðarsdóttir, Anna Elísa (Journal of Childhood, Education and Society, 2022)
In mid-March 2020, leaders of Icelandic preschools faced a new reality: the task of leading and keeping their preschools open during the early stages of a pandemic. Suddenly, everything changed, and dystopia became the “new normal”. The proximal closeness between unrelated people was forbidden, and everyone was supposed to practice social distancing. This article discusses the attitudes of preschool staff towards their leaders (principals) during that time. How successfully did the leaders handle the first weeks of the pandemic? Data were drawn from an online survey conducted between 8 and 18 April 2020 during a time when feelings were running high. The results showed that staff felt that most of the leaders supported and did their best to take care of their staff members. Leaders established new ways to communicate and get information from both staff and parents. They showed assertiveness and used their former leadership training and skills. However, staff perceived leaders had problems setting boundaries, and their insecurity affected their leadership skills. The unique contribution of this study is that its data were collected during the early stages, which may be helpful for later stages or other crises affecting preschools in the future.